America, Russia and the Cold War, 1945-1992 - LaFeber, Walter (New York : McGraw-Hill, 1993)
Rev. ed. of: America, Russia and the Cold War, 1945-1990 6th ed. c1991
Keywords: Cold War; Soviet Union -- Foreign relations -- United States..; United States -- Foreign relations -- Soviet Union; World politics -- 1945.